PERILAKU STICKY COST BIAYA PENJUALAN, BIAYA ADMINISTRASI DAN UMUM SERTA HARGA POKOK PENJUALAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Marhamah, Marhamah; Susanto, Edy; Aminudin, Muhammad (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This study aims to determine the indications of Sticky Cost behavior on Sales, Administration and General Costs and Cost of Sales at Food & Beverage companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The population used is the Food & Beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2016-2018 period, amounting to 27 companies. Independent Variables namely Sales, Administration and General Costs with Cost of Goods Sold. The data analysis technique used is logistic regression analysis. The results showed that Administrative and General Sales Costs had no significant effect on Sticky cost predictions with a significance value of 0.337 <0.05. Cost of Goods Sold does not have a significant effect on Sticky cost predictions with a significance value of 0.411> 0.05. The coefficient of determination is 0.42 or 4.2% Administrative and General Sales Costs and Cost of Goods Sold is able to explain the behavior of Sticky Cost. Â Keywords: Sticky Cost, Administrative and General Sales Costs, Cost of Goods Sold.